A diary study on the moderating role of leader-member exchange on the relationship between job characteristics, job satisfaction, and emotional exhaustion - Poetz, Lennart; Volmer, Judith (Frontiers in Psychology, 2022)
Job characteristics play an essential role for the well-being of employees. When job characteristics are unfavorable, the experienced exchange relationship with one’s supervisor (i.e., leader-member exchange, LMX) may become relevant to weaken negative consequences. We conducted a diary study over ten consecutive working days with 112 academics. Based on conservation of resources theory, we assumed that daily LMX constitutes a resource for employees that moderates the link between job characteristics (job control and time pressure) and job satisfaction as well as emotional exhaustion. Additionally, we proposed lagged-effects of morning job characteristics and LMX on next-day morning job satisfaction and emotional exhaustion. Findings from hierarchical linear modeling (HLM) demonstrated that on the day-level higher perceived levels of job control in the morning were associated with higher perceived job satisfaction and lower perceived emotional exhaustion in the afternoon. The experience of increased time pressure in the morning was negatively related to perceived day-level afternoon job satisfaction and positively to perceived day-level afternoon emotional exhaustion. Within one day, perceived LMX moderated the relationship between perceived job control and perceived job satisfaction in the afternoon. We only found lagged effects of the interaction between afternoon job control and afternoon LMX on next-day morning job satisfaction. We discuss daily LMX as a resource for employees both within one day and from day-to day, along with future research directions on the buffering role of LMX.